Clinical case of applying a safe loading range to a limb in a patient with a femoral neck fracture - O. N. Yamshchikov; S. A. Emelyanov; S. A. Mordovin; E. A. Kolobova; A. V. Grishin; P. M. Teplyakov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Introduction. Currently, most orthopedic traumatologists consider surgical treatment as the method of choice for fractures of the femoral neck. However, despite the constant modernization of the available methods of osteosynthesis, the proportion of unsatisfactory outcomes of surgical intervention and the occurrence of early postoperative complications remains quite high (from 28 to 45%) [1]. One of the main directions for solving the problem of unsatisfactory outcomes of osteosynthesis is the improvement and strict control of measures taken in the postoperative period, including early activation of the patient. Despite the importance of the recovery period, there are still no unified standards for managing patients with hip fractures, and the available treatment protocols contain only a generalized plan for further therapeutic measures that do not take into account the individual characteristics of the patient. We have proposed a method for calculating the optimal load on the limb in the postoperative period. The purpose of this publication is to describe a clinical case of the effective application of the method for determining the optimal range of loads on a limb after surgical treatment of femoral neck fractures.Materials and methods: the study used materials from medical records and instrumental studies of the traumatology department of the TOGBUZ "City Clinical Hospital of Kotovsk", the results of dynamic observation for 12 months in a patient with a transcervical fracture of the femoral neck, for which the method we developed for determining the optimal range was applied. load on the limb after surgical treatment of injury.Results: 12 months after the operation, the patient who used the method for determining the safe load range in the recovery period achieved full functional and anatomical recovery of the operated limb. Full body weight bearing was allowed from the 6th month.Conclusion: the method for determining the safe range of load on the limb after a femoral neck fracture has been tested in practice and led to a positive result, which may indicate its effectiveness.